Potensi Keagamaan Pada Anak Dan Remaja Melalui Program MTQ, Mahasiswa Kuliah Kerja Nyata Di Nagari Batang Arah Tapan - Fadlil Armiadi; Ahmad Khairul Nuzuli; Winda Oktavia (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The Islamic Festival of Musabaqah Tilawatil Quran has become an important part of the Indonesian National Calendar. At IAIN Kerinci, Kukerta students organize the Musabaqah Tilawatil Quran in the Nagari Batang Arah Tapan, aiming to instill Islamic values in the younger generation. This event takes place at the Jamiatul Bilad Mosque in Nagari Batang Arah Tapan and involves children and teenagers. The competition includes contests for teenage recitation, call to prayer, pildacil, memorization of Juz Amma, tartil, funeral prayer, as well as a fashion show featuring Muslim attire. The participants' positive responses reflect their exceptional enthusiasm, which can help enhance their skills and self-confidence. This activity not only provides an opportunity for achievement but also encourages religious development through the innovations it brings forth.